Pendampingan Pelatihan Software Akuntansi Accurate dalam Membantu Guru & Siswa-Siswi Smk untuk Meningkatkan Kompetensi dan Profesionalisme - Paulina Sutrisno; Debora Debora; Nicken Destriana; Ariesta T.K.P.S. Putri; Aan Marlinah; Novia Wijaya; Widyawati Lekok (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: The purpose of this service activity is to equip and assist vocational teachers and students in understanding and being able to operate various features in accurate accounting software related to accounting transactions which are expected to improve the skills of using accounting software for teachers and students. Method: The training method includes an introduction session on accurate accounting software, simulation of the use of accurate accounting software, discussion of journals and financial reports accompanied by questions and answers by vocational teachers and students. Results: Accurate accounting software training went well and smoothly even though it was carried out online, but the enthusiasm of the participants was still intertwined with the many questions asked to the trainers. Conclusions: With this training, it is hoped that it will improve the competence and professionalism of vocational teachers and students in using accurate accounting software which is widely used in companies in Indonesia to produce accounting information that is useful in decision making.